The Relationship between Body Mass Index (BMI) and Leg Muscle Explosive Power with Frog Jump Ability in Grade 6 Students of SDN Buring Malang City - Pratama, Wirayudha; Nurrochmah, Siti (Universitas Hamzanwadi, 2025)
This study aims to understand the extent of the relationship between (IMT) and leg muscle explosion strength on the ability to perform frog jumps in 6th grade male students at SDN Buring, Malang City. This study employs a quantitative descriptive design with an explanatory approach. The population consists of 57 male students. Data collection was conducted using a physical test observation method. The sampling technique used was purposive systematic proportional random sampling, involving 33 male students. Quantitative descriptive statistical methods were used to analyze the data. Furthermore, multiple correlation and regression analyses were conducted to test the strength of the relationship and the extent to which each variable contributed to frog jumping ability. The results showed a significant relationship between BMI and frog jumping ability, with a correlation coefficient of 0.367 and a significance level below 0.05. A stronger relationship was found between lower limb muscle power and frog jumping ability, with a correlation coefficient of 0.862 and a significance level also below 0.05. From these findings, it was concluded that lower limb muscle power has a more dominant influence on frog jumping performance, although BMI also contributes, but not as much as muscle power.